New findings on the taxonomy of the genus Coeleumenes van der Vecht (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species - Mai, Thai Van; Nguyen, Lien Thi Phuong (Zootaxa, 2021)
A new species of the genus Coeleumenes van der Vecht is described from Tay Nguyen highland in southern Vietnam: Coeleumenes chumomray Mai and Nguyen, sp. nov. A key to all known species in the Oriental Region is provided.